PERAN GEOLOGI TEKNIK DAN ANALISIS KEWILAYAHAN DALAM GEOLOGI MILITER DI INDONESIA - Zakaria, Zufialdi (Bulletin of Scientific Contribution, 2005)
Since ancient Chinesse era to World-War 2, knowledge of geoscience hold important role in themilitary world. Landscape analysis (potency and constraint) for military is needed to evaluate enemymovement and its war equipments, to determining access of location rute, to mapping hydrogeologysurface and underground for structural defence & military personnel and also for attack. Though Spot-5,Ikonos and Quickbird sattelite images’ exist, but map of military geology is necessary to remainingsurface material physical characteristic toward teritorial enemy and also to develop defence citadel.Map and scale of military geology based on engineering geology condition for need of military. Variationscale depend on needed, from big scale (most detailed) to small scale (regional).In Indonesia, Indonesian Association of Geologist (IAG) both Geological Research and DevelopmentCenter (GRDC) not had Unit of Military Geology yet. In America, Unit of Military Geology was formedsince 1942. This unit duty is complie terrain intelligence, how troops can be move in land; finding ofwater, fuel, mineral and construction material, solving construction problem and base landing plane.